Synthesis and analysis of a cross-connected Fibonacci dc/dc converter with high voltage gain - Kei Eguchi; Ratanaubol Rubpongse; Akira Shibata; Takaaki Ishibashi (Energy Reports, 2020)
For thermal energy harvester based on a step-up dc/dc converter, we present a cross-connected Fibonacci dc/dc converter and its analysis method in this paper. The topology of the proposed converter has three features: cross-connection of two Fibonacci-type converters, symmetrical design without smoothing capacitors, and inductor-less design by using switched-capacitor (SC) techniques. From these features, high stepped-up voltage which is expressed as a power of two is provided by the proposed converter. Unlike existing converters, the proposed converter achieves small internal resistance as well as small ripple factor, because the output voltage is supplied to an output load in all clock phases. Furthermore, the inductor-less design offers low electromagnetic interference (EMI) noise, small size, and light weight. As an example of the proposed converter, the performance of the proposed converter with 8 voltage gain was evaluated by theoretical analysis, SPICE simulations, and breadboard experiments. Compared with existing dc/dc converters, namely, Fibonacci type converter, series-parallel type, and charge pump, the proposed converter demonstrated high performance in the point of voltage gain, circuit size, power efficiency, and response speed.
Keywords: 330; Cross-connected structure; DC/DC converters; Fibonacci converter; High voltage gain; Inductor-less converters; Symmetrical structure